Consumer management can be overcome! - Šatera, Karel; Dytrt, Zdenek (Univerzita Pardubice, 2014)
Responsible management strives to think creatively, respecting the principles of responsibility and ethics, the objective of which is to establish long-term stability within the business environment. A manager's scope of activities mainly includes decision making related to changes (stimulating innovations) in order to react to dynamic development in the field of science, technology, and the needs and interests of the company. It is extremely important to stimulate employee motivation. Thus it is very logical to speak about leadership as the management process, and its innovations depend on people and their ethical allegiance to the management of the particular system. Opinions vary on the content of leadership. Leadership is most often associated with human resource management. That distorts and simplifies its content, such as innovation management theory and practice. For this reason, the text indicates some significant differences between the still applied management and leadership. Simplifying this concept or misunderstanding its meaning contributes to reducing the effectiveness of innovation and thus to a further deepening of consumer way of thinking of the society. In this text certain differences between management and leadership are indicated.
Keywords: consumerist thinking and behaviour; creative and ethical thinking; responsibility and ethics; responsible management; corporate culture; complexity of management